2014
DOI: 10.1586/14779072.2014.928591
|View full text |Cite
|
Sign up to set email alerts
|

Organization of primary health care for diabetes and hypertension in high, low and middle income countries

Abstract: Chronic non-communicable diseases, predominantly diabetes and cardiovascular disease are a major public health problem globally. The chronicity of these diseases necessitates a restructuring of healthcare to address the multidisciplinary, sustained care including psychosocial support and development of self-management skills. Primary healthcare with elements of the chronic-care model provides the best opportunity for engagement with the health system. In this review, the authors discuss aspects of primary heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
19
0
2
Order By: Relevance
“…Both India and China have committed public funds into healthcare programs for NCDs [29]. China has launched a number of health reforms aimed at improving social health insurance schemes and strengthening primary healthcare [52, 60, 80]. India’s publically-funded health schemes have focused exclusively on inpatient secondary and tertiary care to the neglect of primary healthcare [64] and progress has been impeded by the country’s vast geographic and ethnic diversity [61].…”
Section: Discussionmentioning
confidence: 99%
“…Both India and China have committed public funds into healthcare programs for NCDs [29]. China has launched a number of health reforms aimed at improving social health insurance schemes and strengthening primary healthcare [52, 60, 80]. India’s publically-funded health schemes have focused exclusively on inpatient secondary and tertiary care to the neglect of primary healthcare [64] and progress has been impeded by the country’s vast geographic and ethnic diversity [61].…”
Section: Discussionmentioning
confidence: 99%
“…Primary care can be an effective and cost-effective platform for tackling non-communicable diseases 8 9. However, public primary facilities in India often lack the human resources, diagnostic equipment and drugs to diagnose and treat the nearly 200 million adults living with hypertension in India 10–13.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have expressed hope in finding solutions to the problems of mental health service delivery through mobile phones in the region (Aggarwal, 2012;Brian and Ben-Zeev, 2014). Some studies from India have also reported that health service delivery through mobile phones may be useful in a spectrum of chronic disorders (Dubey et al, 2014;Lall and Prabhakaran, 2014) including mental health (Bali and Singh, 2007;Thara, 2012).…”
Section: Discussionmentioning
confidence: 99%